Utilization of low grade solar energy for vapour compression cycle (VCS) integrated with liquid desiccant dehumidification system (LDAC) - Tay, Zeng Hao (2016)
The report discusses and compares conventional air conditioning systems to the liquid desiccant air conditioning (LDAC) systems. In recent years, it has come to light that a larger focus should be placed on LDAC for its energy conserving abilities as it is able to make use of low grade waste heat as a main source of energy. In addition, various forms and types of liquid desiccants will be looked into to determine which would be the most efficient and suitable one to be utilised in the dehumidification process. Despite its corrosive power, one of the most common desiccant solution to be used in LDAC is Lithium chloride. In order to overcome this corrosive aspect of LiCl, plastic plate heat exchanges were introduced in the system. The simulation program ‘TRNSYS’ will be able to utilize the values gathered from the heat transfer coefficient of the plastic plate heat exchanger. The project is primarily focused on a simulation that integrates the existing vapour compression system with the liquid desiccant dehumidifying system while taking Singapore’s climate into perspective. The model set up is done through ‘TRNSYS’ – a simulation software – that will be able to determine the ideal values for the operating parameters. Numerous references and assumptions are made on the power ratings of the components used in the simulation in order to derive at the results. The results are also compared with the experimental data. It is proven, through both the simulation and experimental results that the hybrid system is energy efficient and compared to the conventional air conditioning system. The amount of energy saved from the vapour cooling system is 24.9% while the energy saved from the cooling load is found to be 46.5%.